If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M * m + -3m = 18 Multiply M * m mM + -3m = 18 Reorder the terms: -3m + mM = 18 Solving -3m + mM = 18 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Reorder the terms: -18 + -3m + mM = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + -3m + mM = 0 The solution to this equation could not be determined.
| -2x+3=-5x+6 | | 5y-9=8y-4y | | 9.7+x=11.24 | | 9x-5=2x+3 | | 4(5)+-20=0 | | 3x-2k=24x-16 | | 5x(x+12)=-180 | | 12.25+x=13.11 | | -2/p=4/11 | | 6x-84=3x-9 | | 3x(x+12)=2x(2x+4) | | -5+7x=3+9x | | n/5-5=7 | | -21z-33=30 | | 6x-4+6-2x=12 | | 5.2(2a-1)=7 | | 2h-12=2 | | -7x-24=312 | | 2x+40x= | | 4x-15(6-x)=-8(5-3x) | | -20p-5=-765 | | 77=5y-13 | | 16=4s-4 | | 9x+4.86=3x+12 | | 10x^2-50x-60=0 | | 7x-13=4x-4 | | 7a=10 | | 4y+70=6 | | 4u-10=24 | | 4x-15(6-x)=8(5-3x) | | 3r-7s=K | | 6/x=24/(30-2x) |